Peningkatan Daya Dukung Lempung Ekspansif Dengan Pondasi Bambu Di Daerah Krebet Dan Sekitarnya, Kabupaten Kulon Progo, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Krebet area is located in Desa Tuksono, Sentolo, Kulon Progo, Yogyakarta. In this area, a lot of residential buildings were damaged which is caused by expansive days. Many floor slabs constructed on an expansive days area crack and heave which is followed by damaging windows, doors, and wall crackings. In order to study the preventive method for residential building damage, the characteristics of some engineering properties and mineralogical composition of clay was identified by test and observation in the field and laboratory. The uses of each test and observation were emphasized for structural stability analysis. . The observation and considerable detail of fieldwork were takenplace in three locations of test pits. The value of undrained shear strength was low (12 kg/cm2 - 24 kg/cm2). It caused the bearing capacity of day, as withholding force, was smaller then the uplifting force. The analysis of structural stability showed that the bearing capacity of day could be increased by three types of foundations. Two layers of raft foundation can reinforce the bearing capacity of day up to 0.50 - 0.93 meter thick, pile foundation up to 0.50 - 1.54 meter thick, and pile foundation with wings up to 0.50 - 2.36 meter thick. One layer raft foundation was not recommended because its capability was still in the tolerance of uplift movement (0.5 - 0.87). The grandstand is recommended when the foundations can not reinforce all of thickness of clay in the study area.